Arc temperature profile measurement and characteristic analysis on an SF6 high‐voltage CB. Issue 12 (19th March 2018) - Bai, Su; Guan, Yonggang; Luo, Haiyun; Liu, Weidong
Abstract : The arc temperature profile in an interrupter, which determines the extinguishing characteristic of an SF6 circuit breaker (CB), is of interest to designers and developers. In this investigation, optical fibres and spectrograph were employed to measure the arc temperature profiles in a 252 kV SF6 CB during short current interrupting. The temperature profiles of the upstream, throat, and downstream of the nozzle have been measured. The optical fibres can transfer the arc light from the measuring points in the nozzle to the spectrograph. Moreover, the spectral line intensities of copper (Cu) 510.5, Cu 515.3, and Cu 521.8 nm were obtained by the spectrograph. The condition in CB can be treated as a local thermal equilibrium system, and the temperature profiles can be calculated by two‐line method and Abel inverse method. The arc temperature profiles of the interrupter under 15–50 kA root mean square current have been analysed through the method established in this investigation.